Integration of Innovative Management Systems and Tourism Distribution Channels (Economics and region, 2018)
The problems of reforming the tourism distribution are under consideration. The necessity of implementing innovation in the tourism information management system as a guarantor of its competitiveness is substantiated. The prospects of the integration of innovative information system and the distribution channels are determined
Keywords: innovation; information management system; distribution channel; competitiveness